Proceeding of International Conference on Islamic Education (ICIED) 2015 - Ali, at all, Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 1 No 1 (2015): Proceeding of International Conference on Islamic Education (ICIED), 2015)
This proceeding is compilation of 62 selected papers written in Arabic, English and Indonesian languages from the first International Conference of Islamic Education in Southeast Asia: Reforms, Prospects and Challenges on December, 2015. There are 22 papers accentuating the topics of the Aims and Model of Islamic Education, 23 papers explore the topic of Teaching Experiences from Classroom in Islamic Education in Islamic Education Institutions and the rest, 18 presenters are ready to palpably share their perspectives on the Reforming Islamic Institution in an Era of Globalization.